Local food systems and community economic development through the lens of theory. Issue 5 (19th October 2016) - Christensen, Bradley; Phillips, Rhonda
Abstract: The premise of this article is that community support for local food systems and agriculture enterprises represents a convergence of both community and economic development approaches. By drawing on theory for understanding how local food systems and agriculture enterprises are pursued, there are lessons offering understanding and guidance for actions to support more holistic community economic development (CED) approaches. Using theory as a foundation, we seek to articulate the relationships between local food systems, agriculture enterprises, and CED, providing Hardwick, Vermont, as our case study. We seek to explore four theories: social capital, conflict theory, symbolic interaction, and rational choice. It is our intent to show that theory can provide insight for action and deepen understanding of local food system changes and CED impacts.